A Co-Integration Analysis of the Interdependencies between Crude Oil and Distillate Fuel Prices - Aduda, Jane; Weke, Patrick; Ngare, Philip (Scientific Research Publishing, 2018)
The co-evolution and co-movement of financial time series are of utmost importance in contemporary finance, especially when considering the joint behaviour of asset price realizations. The ability to model interdependencies and volatility spill-over effects introduces interesting dimensions in finance. This paper explores co-integrating relationships between crude oil and distillate fuel prices. Existence of multivariate co-integrating relations and bidirectional Granger-Causality is established among the series. It is also established that even after fitting a full VECM, the residuals are not necessarily multivariate normal suggesting the noise could as well be multivariate GARCH.
Keywords: Co-Integration; Futures and Spot Prices; Granger-Causality; ECM; VECM; Volatility Spill-Over; Johansen’s Test; Engle-Granger Test